Adenosine Receptor and Its Downstream Targets, Mod(mdg4) and Hsp70, Work as a Signaling Pathway Modulating Cytotoxic Damage in Drosophila - Lin, Yu-Hsien; Maaroufi, Houda Ouns; Kucerova, Lucie; Rouhova, Lenka; Filip, Tomas; Zurovec, Michal (Frontiers in Cell and Developmental Biology, 2021)
Adenosine (Ado) is an important signaling molecule involved in stress responses. Studies in mammalian models have shown that Ado regulates signaling mechanisms involved in ‘danger-sensing’ and tissue-protection. Yet, little is known about the role of Ado signaling in Drosophila. In the present study, we observed lower extracellular Ado concentration and suppressed expression of Ado transporters in flies expressing mutant huntingtin protein (mHTT). We altered Ado signaling using genetic tools and found that the overexpression of Ado metabolic enzymes, as well as the suppression of Ado receptor (AdoR) and transporters (ENTs), were able to minimize mHTT-induced mortality. We also identified the downstream targets of the AdoR pathway, the modifier of mdg4 (Mod(mdg4)) and heat-shock protein 70 (Hsp70), which carry out its function. Finally, we showed that a decrease in Ado signaling affect other Drosophila stress reactions, including paraquat and heat-shock treatments. Our study provides important insights into how Ado regulates stress responses in Drosophila.